Pengaruh Harga dan Kualitas Layanan terhadap Kepuasan Pengguna Gojek: Analisis Kuantitatif Di Kota Medan - Sitompul, Philips Rikardo (Asosiasi Dosen Akuntansi Indonesia, 2024)
This study aims to evaluate the impact of service quality and pricing on Gojek customer satisfaction in Medan. The study is quantitative, so a questionnaire is used. A quantitative approach was used for the survey, with one hundred active Gojek users participating. The study shows that customer satisfaction is related to price and service quality. Customers rated service quality as punctual, convenient, courteous drivers, and transparent pricing. Using these research findings, Gojek can create strategies to improve service quality and retain customers